Bola@UiTM: Mobile application for UiTM football club event / Mifzal Najwan Najmi - Najmi, Mifzal Najwan (2021)
Football is one of the most popular sports around the world. There are many popular football clubs around the globe. These popular football clubs are taking the advantage of changes of technology that allow people to develop something that can help them in daily basis such as the existence of football club application that have reservation football match ticket and online payment features. UITM also have their own football club named UITM FC. For the time beings, UITM FC does have only social media such as Facebook, Twitter, and Instagram as their platform to spread the news regarding UITM FC. When there is a football match involving UITM FC, the supporters need to queue long in order to buy the football match ticket. Hence, this project of Bola@UITM Mobile Application is developed to ease the process of reservation football match ticket. The project aims to identify user requirements of a mobile application. To fulfil the project requirements, a method of Mobile Application Development Life Cycle (MADLC) is used. The target of this project is UITM Shah Alam students and UITM FC organizer. All user requirement regarding this project was obtained through an interview session with some students who have experience during bought the football match ticket at the stadium counter. Another interview session was conducted with Sport Assistant, Pusat Sukan UITM to gather the requirement needed. Next, this mobile application was developed based on the design and features needed. Right after the implementation of mobile application assessment through the analysis requirement is done, the process of designing a prototype interface was made. Method of storyboard such paper-based was applied through this project to give an idea on how the application would look like. The prototype was then created using Marvel application. Apart from that, another interview session was made to observe an evaluation on how students would use Bola@UITM Mobile Application. The result is then lead to improvement for future works.